2018
DOI: 10.1002/jssc.201800663
|View full text |Cite
|
Sign up to set email alerts
|

Rapid ultrasound‐assisted dispersive solid‐phase extraction of nonsteroidal anti‐inflammatory drugs in urine using oleic acid functionalized magnetic graphene oxide

Abstract: We describe an ultrasound‐assisted magnetic dispersive solid‐phase extraction based on oleic acid functionalized magnetic graphene oxide followed by high‐performance liquid chromatography with ultraviolet detection. The method was applied for the simultaneous determination of ibuprofen, diclofenac, naproxen, and mefenamic acid in urine. The application of sonication led to the good dispersion of the sorbent, and consequently, significant shortened the extraction time. The sorbent was successfully characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 36 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…23 Surface-modied magnetic nanoparticles can be combined with different stationary phases, and these modied magnetic particles can be easily separated from the medium by using simple magnets. 24,25 Studies have shown that magnetic nanomaterials have gained signicant interest due to their large specic surface area, selective absorption, and surface modications. [26][27][28] In fact, biosorbents are combinations of biomass materials and magnetically active metal or metal oxide nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…23 Surface-modied magnetic nanoparticles can be combined with different stationary phases, and these modied magnetic particles can be easily separated from the medium by using simple magnets. 24,25 Studies have shown that magnetic nanomaterials have gained signicant interest due to their large specic surface area, selective absorption, and surface modications. [26][27][28] In fact, biosorbents are combinations of biomass materials and magnetically active metal or metal oxide nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, various detection technologies are used to measure the levels of molecules and metabolites in urine and other fluids in order to identify the specific biomarkers of diseases which provide a new perspective for the research on the relationship between dietary, drugs, and diseases [16]. Namera et al [17] analyzed a method that was developed for the detection of arsenite, arsenate, and methylarsenate in human urine by GC-MS. Seidi et al [18] developed a more rapid, sensitive, and practical CE-C4D method based on SPE purification for the analysis of the urine metabolites, oxalate, and citrate in urine samples from patients. Ion chromatography (IC) is a form of HPLC, which is a method used to analyze the presence and levels of anions, cations, and small molecule polar organic compounds [19].…”
Section: Introductionmentioning
confidence: 99%
“…Seidi et al. [18] developed a more rapid, sensitive, and practical CE–C4D method based on SPE purification for the analysis of the urine metabolites, oxalate, and citrate in urine samples from patients. Ion chromatography (IC) is a form of HPLC, which is a method used to analyze the presence and levels of anions, cations, and small molecule polar organic compounds [19].…”
Section: Introductionmentioning
confidence: 99%
“…The sample pre-treatment processes, such as enrichment, concentration, and purification of NSAIDs in environmental samples are frequently required to improve the detection sensitivity and accuracy [14]. The sample pretreatment methods include liquidliquid extraction [15,16], dispersion extraction [17][18][19], SPME [20], and solid-phase column extraction [21][22][23][24]. The thin-film extraction can reduce the consumption of organic solvent.…”
Section: Introductionmentioning
confidence: 99%